Seaweed Extracts Enhance Salam Turfgrass Performance during Prolonged Irrigation Intervals and Saline Shock - Elansary, Hosam O.; Yessoufou, Kowiyou; Abdel-Hamid, Amal M. E.; El-Esawi, Mohamed A.; Ali, Hayssam M.; Elshikh, Mohamed S. (Frontiers in Plant Science, 2017)
The negative effects of the ongoing climate change include unusual prolonged droughts and increased salinity pressures on the agricultural lands. Consequently, crops are facing unprecedented environmental pressure, and this calls for more research towards controlling such major stresses. The current study investigates the effects of seaweed extract sprays of Ascophyllum nodosum (5 and 7 mL.L-1; 6-day intervals) on Paspalum vaginatum Salam՚ during prolonged irrigation intervals (2 and 6 day) and saline growing conditions (1 dS.m-1 and 49.7 dS.m-1) for 6 weeks in containers under greenhouse conditions. Control plants showed reduced turf quality, photochemical efficiency, root length and dry weight, total nonstructural carbohydrates and K and Ca compositions. Seaweed extracts increased turf quality, leaf photochemical efficiency, root length and dry weight, total non-structural carbohydrates, K, Ca and proline in treated plants during prolonged irrigation intervals as well as saline shock conditions. There were also increases in the antioxidant defensive mechanisms such as superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) activities and non-enzymatic antioxidants as well as reduced lipid peroxidation. The application of SWE at 7 mL.L-1 showed higher performance in treated plants during prolonged irrigation intervals as well as saline conditions. Our findings imply that several mechanisms including drought tolerance, osmotic adjustment and antioxidant defense system may interact to enhance the performance of plants in the face of environmental stress following SWE treatments.